The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.eujim.2020.101101
|View full text |Cite
|
Sign up to set email alerts
|

Overview on pattern identification – History, nature and strategies for treating patients: A narrative review

Abstract: Introduction: In traditional East Asian Medicine (TEAM), various systems of practice exist that have used different theories to guide their practice. Although data gathering has been limited to what can be observed by the four examinationssi zhen, the different systems of practice have focused on different observational data to make diagnostic decisions and choose corresponding treatments. The organization of the data into patterns has led to what is called Pattern Identification based systems of practice (PIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Few therapeutic options offer a mixed-evidence based approach like this. It may also be advantageous if traditionally based practice 108 is used since emerging evidence supports the performance of TEAM diagnostic evaluations and treatments in palliative care. A recent study found that the diagnostic patterns were predictors for response in hot flashes in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Few therapeutic options offer a mixed-evidence based approach like this. It may also be advantageous if traditionally based practice 108 is used since emerging evidence supports the performance of TEAM diagnostic evaluations and treatments in palliative care. A recent study found that the diagnostic patterns were predictors for response in hot flashes in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the use of phytomedicine has become an essential type of therapy in our modern life due to its importance in the treatment and prophylaxis of several illnesses [ 1 ]. Obviously, their use has existed since ancient civilizations and has been utilized as conventional and complementary types of therapies [ 2 ]. Moreover, due to their influence on many systems in the human body, most of the prescribed medicines nowadays are originated from plants [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…TCM is a complex system of practice that has combined different treatment systems (e.g., herbs and acupuncture) into one with a single diagnosis system. 5,9 While in Japan, the diagnostic processes and patterns for herbal medicine and acupuncture are different, 10 which is understandable given that they have been practiced separately for a long time. 5 It is probable that the types of diagnoses for the different systems are likely to be different due to differences in how they act and changes that can be observed, 11,12 which raises the question of whether a single diagnosis system can precisely capture the details of different systems of practice (herbs and acupuncture) and to what extent this may introduce problems in establishing DA for TCM?…”
mentioning
confidence: 99%
“…This may at first seem to be a strange question, but it is relevant because there are TEAM practice systems where the diagnosis is routinely arrived at without discussion of or use of the symptoms of the patient to decide the pattern of diagnosis. 10 There are also systems that usually include the symptoms of the patient when deciding the pattern of diagnosis 10 and there are systems that seek a diagnosis that explains why the symptom occurs, 13 so that the pattern is based on a limited subset of patterns that could explain the origin of the symptom. 8,10 To understand the role of symptoms in deciding the pattern in a specific system of practice, literature reviews and surveys of practice need to be conducted.…”
mentioning
confidence: 99%
See 1 more Smart Citation